Highly Water-Soluble Solid Dispersions of Honokiol: Preparation, Solubility, and Bioavailability Studies and Anti-Tumor Activity Evaluation - Li Wang; Weiwei Wu; Lingling Wang; Lu Wang; Xiuhua Zhao (Pharmaceutics, 2019)
Honokiol (HK), a well-tolerated natural product, has many multiple pharmacological activities. However, its poor water solubility and low bioavailability limit its clinical application and development. The aim of this research was to prepare the solid dispersion (SD) formulation of honokiol (HK) with poloxamer-188 (PLX) as the carrier, thereby improving its solubility and oral bioavailability. Firstly, by investigating the relationship between the addition amount of the PLX and the solubility of HK, and the effects of solid dispersions with different ratios of HK−PLX on the solubility of HK, we determined that the optimum ratio of PLX to HK was (1:4). Then, the HK−PLX (1:4) SD of HK was prepared using the solvent evaporation method. The morphology of the obtained HK−PLX (1:4) SD was different from that of free HK. The HK in the HK−PLX (1:4) SD existed in amorphous form and formed intermolecular hydrogen bonds with PLX. Additionally, the solubility values of the HK−PLX (1:4) SD were about 32.43 ± 0.36 mg/mL and 34.41 ± 0.38 mg/mL in artificial gastric juice (AGJ) and in artificial intestinal juice (AIJ), respectively. Compared with free HK, the release rate and the bioavailability was also substantially improved for HK in its SD form. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay indicated that the HK−PLX (1:4) SD showed higher inhibition of HepG2 cells than free HK. Taken together, the present study suggests that the HK−PLX (1:4) SD could become a new oral drug formulation with high bioavailability and could produce a better response for clinical applications of HK.